Association between intraoperative dexmedetomidine and all-cause mortality and recurrence after laparoscopic resection of colorectal cancer: Follow-up analysis of a previous randomized controlled trial - Hu, Jingping; Gong, Chulian; Xiao, Xue; Chen, Liubing; Zhang, Yihan; Li, Xiaoyue; Li, Yanting; Zang, Xiangyang; Huang, Pinjie; Zhou, Shaoli; Chen, Chaojin (Frontiers in Oncology, 2023)
Background Dexmedetomidine (DEX) has been widely applied in the anesthesia and sedation of patients with oncological diseases. However, the potential effect of DEX on tumor metastasis remains contradictory. This study follows up on patients who received intraoperative DEX during laparoscopic resection of colorectal cancer as part of a previous clinical trial, examining their outcomes 5 years later. Methods Between June 2015 and December 2015, 60 patients undergoing laparoscopic colorectal resection were randomly assigned to the DEX and control groups. The DEX group received an initial loading dose of 1μ/kg before surgery, followed by a continuous infusion of 0.3μg/kg/h during the operation and the Control group received an equivalent volume of saline. A 5-year follow-up analysis was conducted to evaluate the overall survival, disease-free survival, and tumor recurrence. Results The follow-up analysis included 55 of the 60 patients. The DEX group included 28 patients, while the control group included 27 patients. Baseline characteristics were comparable between the two groups, except for vascular and/or neural invasion of the tumor in the DEX group (9/28 vs. 0/27, p = 0.002). We did not observe a statistically significant benefit but rather a trend toward an increase in overall survival and disease-free survival in the DEX group, 1-year overall survival (96.4% vs. 88.9%, p = 0.282), 2-year overall survival (89.3% vs. 74.1%, p = 0.144), 3-year overall survival (89.3% vs. 70.4%, p = 0.08), and 5-year overall survival (78.6% vs. 59.3%, p = 0.121). The total rates of mortality and recurrence between the two groups were comparable (8/28 vs. 11/27, p = 0.343). Conclusion Administration of DEX during laparoscopic resection of colorectal cancer had a nonsignificant trend toward improved overall survival and disease-free survival. Clinical Trial Registration http://www.chictr.org.cn/, identifier ChiCTRIOR-15006518.